Tinjauan Penerapan Pendaftaran Online Pasien Rawat Jalan di RS Yadika Kebayoran Lama - Meliana Meliana; Joko Asmoro Widhi; Royda Syarafina (Poltekkes Kemenkes Semarang, 2022)
Outpatinet registration where the patient first meets the staff directly at the health facility. The application of registration is expected to use technology to make work of medical recorders more effective and efficient to reduce existing problems. The purpose of this study was to obtain an overview of the application of an outpatient online registration system. knowing the procedure (SPO) for implementing an outpatient online registration system, knowing the implementation of an outpatient online registration system, knowing the obstacles to implementing an outpatient online registration system at Yadika Kebayoran Lama Hospital. The research method used is descriptive research method. With the observation data collection method by involving participant observation, namely patients who register for outpatient treatment using an interview sheet. From the results of the research conducted by the author in the registration section that Yadika Hospital does not have a special SPO related to outpatient registration, the time for outpatient registration services starting from patients registering to getting the majority queue number is less than five minutes. The percentage of outpatient registration service time 5 minutes is 4.21% while the percentage of outpatient registration service time 5 minutes is 95.97%. The online registration system has not been implemented because it has not received approval from Head Quarter the reason is no application to verify patient registration. Suggestions from the author should start compiling SOPs related to online patient registration. Hospitals need to prepare an online registration application so that it is immediately approved for use by the center and the implementation of the registration system can be operated consistently.